Necesidad de insertar la imprescriptibilidad de los delitos contra el ambiente y la naturaleza o pacha mama, en el código orgánico integral penal - Román Ordóñez, Jimy Wagner (2015)
The Constitution of the Republic of Ecuador, between freedom rights that it recognizes people, it provides the right to live in a healthy, ecologically balanced and pollution-free environment, this purpose has typified the Integral Penal organic code, some behaviors under the heading of environmental crimes, which seeks to punish all those unlawful behaviors that affect the stability and ecological balance. One of the powerful agents of contamination, which is present in Ecuadorian society due to the development of activities such as industry, farming based on the use of chemical products and the creation of health institutions that generate hospital waste, and the development of big cities in the country, and in other areas of Latin American or European in a greater degree of population growththey generate tons of garbage, which is called pollution by waste; However when reviewing the legal regime of the organic comprehensive criminal code, on this type of pollution observed that the penalties envisaged is too mild, and bears no proportion to the severity of the damage caused.. In addition, is has been able to determine that in accordance with the rules of the criminal code, illicit behaviors listed as environmental crimes, are prescriptibles by the lapse of time, both in regards to the action as a worthwhile to pursue those responsible, legal criteria which is inappropriate since it generates impunity by subsequent consequences of the Commission of an environmental offence. Consequently develops a legal problem that has been chosen to be addressed in this research work, which has entitled it is: "Need of insert LA IMPRESCRIPTIBILIDAD of LOS crimes against the environment and the nature or PACHA MAMA in the organic INTEGRAL PENAL code".. Study provides a conceptual, doctrinal and legal base as well as the result of field research, allowing to effectively conclude and verified the investigated problem, for what at the end of this document the presentation of the proposed legal reform becomes the Integral penal organic code, which seeks to better guarantee the right to live in a healthy environmentagainst contamination by waste generating illicit behavior, and environmental crimes in general